Investigating sport tourists’ perceived attributes of Muay Thai, event satisfaction and behavioural intentions of attending future events - Popa, Arporn; Yusof, Aminuddin; Soh, Kim Geok (Human Resource Management Academic Research Society, 2017)
The purpose of this study was to investigate which determinants of the theory of planned behaviour (attitudes, subjective norms and perceived behavioural control), perceived attributes and event satisfaction are the best predictors of behavioural intentions in attending future Muay Thai events in Thailand. Data were collected from 209 subjects comprising of foreign sport tourists who attended Muay Thai events at Sanam Muay Rajadamnern stadium and Sanam Muay Lumpini stadiums in Thailand. The questionnaire consisted of instruments modified from Ferreira and Armstrong (2004), Shonk (2006) and Cunningham and Kwon (2003). The finding indicated that subjective norm (R2change = .251) or 25.1% of the total variance was the best predictor of tourists’ behavioral intentions in attending future Muay Thai events, followed by game attractiveness (R2change = .045), perceived behavioral Control (R2change = .037), cost (R2change = .025), and event satisfaction (R2change = .019). The results of the study were discussed in light of earlier findings concerning of intending sports events.